Penerapan Tahsinul Qur’an dalam Mengajar TPA di Dusun Gunung Batu Desa Pampangan - Alif, Muhamad Nur (CV. ULIL ALBAB CORP, 2024)
This research is motivated by the large number of children nowadays, more specifically in rural areas, where there are still children who cannot read the Al-Quran in accordance with the educational foundation of tajwid and tahsin. If from an early age you have not been able to read the Al-Quran using the knowledge of recitation and tahsin, then when you grow up it will certainly be difficult to understand the laws of reading contained in the Al-Quran. TPA (Al Qur'an Education Park) is a place where parents place their trust so that their children learn and teach religious knowledge, especially how to read the Koran. However, this is still not optimal because some of the teachers there have not practiced recitation and tahsin learning. Therefore, we took the initiative to record what the quality of TPA students in Gunung Batu Hamlet is like, so that friends who read this article and have good abilities through knowledge, affiliation, etc. can also help develop and advance TPA in Pampangan Village for the better.